2012
DOI: 10.17221/5920-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of service sire on litter size traits in Czech Large White and Landrace pigs

Abstract: Litter size traits generally are lowly heritable (Hanenberg et al., 2001;Wolf et al., 2002;Chen et al., 2003). Therefore, using additional information in genetic evaluations may be beneficial for increasing the precision of predicted breeding values. A potential source of information is the effect of service sire. According to van der Lende et al. (1999), service sire can influence both fertilization rate and prenatal survival rate. Such an effect could be due to genetically determined differences in fertilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Moreover, Chen et al [ 2 ] estimated a higher variation due to service sire effects relative to the values of 3.0% to 4.0% reported in the present study for NBA in Duroc, Landrace, and Yorkshire breeds. Wolf and Wolfova [ 8 ] also reported that 2.0% to 3.0% of the variance was due to service sire effects in Czech Large White, while they were responsible for 2.0% of the variance in Czech Landrace for TNB and NBA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Chen et al [ 2 ] estimated a higher variation due to service sire effects relative to the values of 3.0% to 4.0% reported in the present study for NBA in Duroc, Landrace, and Yorkshire breeds. Wolf and Wolfova [ 8 ] also reported that 2.0% to 3.0% of the variance was due to service sire effects in Czech Large White, while they were responsible for 2.0% of the variance in Czech Landrace for TNB and NBA.…”
Section: Resultsmentioning
confidence: 99%
“…However, small reductions in heritability in all breeds were observed when service sire effects were added to the model. Models with or without service sire effects are recommended for genetic evaluation of litter traits [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolf and Wolfova (2012a) examined the impact of including a service sire effect on litter size traits for Czech Large White and Czech Landrace sows. Three different animal models were evaluated for each litter size trait (total number of piglets born, born alive and weaned): (i) the service sire effect was included and the complete relationship matrix for all the animals (service sires and sows) was taken into account; (ii) the service sire effect was included as a random effect without inclusion of the relationship matrix; (iii) the service sire effect was omitted from the model.…”
Section: Pigsmentioning
confidence: 99%
“…A flexible allocation of records to herd-year-season classes was applied as first described in Wolf et al (2005) and adapted for litter size traits in Wolf and Wolfová (2012). Herd-year-season classes preferably were formed according to natural seasons (spring, summer, autumn, winter) on the basis of the farrowing date and normally had a length of three months.…”
Section: Datamentioning
confidence: 99%